Social structure in Hallstatt burial mounds – how far can we go? - Potrebica, Hrvoje (2013)
The paper concentrates on features of burial mounds which are usually related to ideas of social status and social role of the deceased. Based on several case studies from the Eastern Hallstatt Circle the author will try to show that these features are not simple reflections of the social structure of local communities and that such generalisations can be quite misleading. The level of relation of mound construction and grave inventories to social structure of the community which raised them, in large extent depends on spatial and temporal context of these monuments which is significantly different in different cultural groups of the Eastern Hallstatt area.